2019
DOI: 10.1371/journal.pone.0220642
|View full text |Cite
|
Sign up to set email alerts
|

The long-term consequences of antibiotic therapy: Role of colonic short-chain fatty acids (SCFA) system and intestinal barrier integrity

Abstract: Epidemiological studies revealed that antibiotics exposure increases a risk of inflammatory bowel diseases (IBD) development. It remained largely unknown how antibiotic-induced dysbiosis confers the risk for enhanced inflammatory response. The aim of the present study was to test the hypothesis that SCFAs, their receptors and transporters mediate the antibiotic long-term effects on the functional state of colonic mucosa and susceptibility to the experimental colitis. Male Wistar rats were treated daily for 14 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
60
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(66 citation statements)
references
References 89 publications
3
60
1
2
Order By: Relevance
“…The observed increase in goblet cell numbers is in agreement with a previous study showing that administration the boardspectrum antibiotic ceftriaxone to Wistar rats causes increased goblet cell numbers and size (Holota et al, 2019). It is well established that bacterial colonization affects mucin gene expression, and in agreement with the present study, a negative correlation between abundance of Lactobacillus spp.…”
Section: Discussionsupporting
confidence: 93%
“…The observed increase in goblet cell numbers is in agreement with a previous study showing that administration the boardspectrum antibiotic ceftriaxone to Wistar rats causes increased goblet cell numbers and size (Holota et al, 2019). It is well established that bacterial colonization affects mucin gene expression, and in agreement with the present study, a negative correlation between abundance of Lactobacillus spp.…”
Section: Discussionsupporting
confidence: 93%
“…It has been reported that the impact of antibiotics on the gut microbiome can be attributed to its antimicrobial spectrum and the antimicrobial activity in the colon depending on concentrations [ 46 , 47 ]. Previous studies examined the effect of several types of antibiotics on the perturbation of gut microbiota, which may lead to an alteration in colonic mucosal homeostasis and microbial metabolites [ 18 , 27 , 48 , 49 ]. Høverstad et al reported that considerably changed SCFA profiles were observed according to the administration of ampicillin (500 mg four times daily) in the human clinical trial [ 46 ].…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies demonstrated that the dysbiosis of the gut microbiota is linked to metabolic disease through changes to microbiota-derived metabolites, including volatile fatty acids (VFAs) via fermentation [ 17 ]. Microbial VFAs have beneficial effects in protecting intestinal epithelial barrier integrity and against intestinal inflammation [ 18 ]. In general, VFAs include a group of aliphatic monocarboxylic acids with different lengths of the chain containing from 2 to 7 carbon atoms, namely acetic (C 2 ), propionic (C 3 ), iso-butyric and butyric (C 4 ), iso-valeric and valeric (C 5 ), iso-caproic and hexanoic (C 6 ), and heptanoic (C 7 ) acids [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, many nano-delivery systems use pH-sensitive polymeric materials to target the microbiota with antibiotic drugs. 79,80 Synthetic polymers, including poly (acrylic acid), poly (acrylamide), poly (diethyl-aminoethyl methacrylate), poly (dimethyl-aminoethyl methacrylate), and poly (methacrylic acid), have been widely studied for the construction of pH-sensitive antibiotic nano-drugs that yield enhanced antimicrobial effects through sustained drug release. 81 Some natural polymers, including albumin and gelatin, have also been tested for the production of efficient pH-susceptible nanosystems that can improve the antimicrobial efficiency of antibiotics (i.e., ciprofloxacin, aminoglycosides) by ensuring a targeted and controlled release.…”
Section: Microbiotamentioning
confidence: 99%